Clad steel plate, its manufacturing method and line pipe

By employing a bainite-based structure and specific composition controls in clad steel sheets, the challenges of achieving low-temperature toughness and high tensile strength in thick materials are addressed, resulting in clad steel sheets with enhanced mechanical properties and corrosion resistance.

JP7666753B1Active Publication Date: 2025-04-22JFE STEEL CORP
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2024546307
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2023-06-05
Filing Date
2024-04-11
Publication Date
2025-04-22
Estimated Expiration
2044-04-11

AI Technical Summary

Technical Problem

Existing technologies face challenges in ensuring sufficient low-temperature toughness in clad steel sheets, particularly in thick materials over 30 mm, while maintaining high tensile strength and bondability.

Method used

The development of a clad steel sheet with a bainite-based structure in the base steel sheet, where the area ratio of bainite is 80% or more and the average crystal grain size is less than 20 μm, along with a Ni-based alloy or austenitic stainless steel as the combined material, using specific composition controls and manufacturing processes such as hot rolling, quenching, and tempering.

Benefits of technology

This approach achieves clad steel sheets with tensile strength of 535 MPa or more, excellent HAZ toughness, and high ductile fracture ratio at -30°C, while maintaining good bondability and corrosion resistance, even in thick materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007666753000001
    Figure 0007666753000001
  • Figure 0007666753000002
    Figure 0007666753000002
  • Figure 0007666753000003
    Figure 0007666753000003
Patent Text Reader

Abstract

Even if the plate thickness is over 30 mm, the tensile strength is 535 MPa or more, and DWTTSA -30℃ The present invention provides a clad steel plate having excellent HAZ toughness and a manufacturing method thereof, in which the hardness is 85% or more and the hardness is 85% or more. A clad steel plate having a clad material bonded to one or both sides of a base steel plate, the base steel plate containing predetermined amounts of C, Si, Mn, P, S, Al, Nb, Ti, and N, and further containing predetermined amounts of one or more elements selected from Cu, Ni, Cr, Mo, V, and Ca, and having a chemical composition that satisfies 0.40≦Ceq≦0.50 with the balance consisting of Fe and unavoidable impurities, the base steel plate having an area ratio of 80% or more of bainite at a 1 / 2 position in the plate thickness direction of the base steel plate, and having a steel structure in which the average crystal grain size of the bainite is less than 20 μm.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a clad steel plate and a manufacturing method thereof, in particular, to a clad steel plate suitable for a line pipe and a manufacturing method thereof.The present invention also relates to a line pipe using the clad steel plate. [Background technology]

[0002] A clad steel plate is a steel plate in which a base steel plate such as carbon steel is laminated with a cladding material made of a corrosion-resistant alloy. Such clad steel plates have the mechanical properties and corrosion resistance required for structural components, and are advantageous in that they are less expensive than solid corrosion-resistant alloy materials.

[0003] In recent years, oil and natural gas development has expanded into areas exposed to severe corrosive environments. Accordingly, the demand for line pipes that enable economical transportation of oil and natural gas is expected to increase. And, due to their high corrosion resistance, clad steel plates, especially Ni-based alloy clad steel plates and austenitic stainless clad steel plates, are expected to be in demand for line pipes exposed to severe corrosive environments.

[0004] Here, clad steel plates for line pipes are required to ensure not only the corrosion resistance of the cladding material but also predetermined mechanical properties, particularly excellent low-temperature toughness from the viewpoint of preventing brittle fracture of pipelines.

[0005] As such a clad steel plate, for example, Patent Document 1 describes: "In a clad steel plate having a Ni alloy as a cladding material and a low alloy steel as a base material, the chemical components of the base material are, in mass%, C: 0.020 to 0.100%, Si: 0.10 to 0.50%, Mn: 0.75 to 1.80%, P: 0.015% or less, S: 0.0030% or less, Cu: 0.01 to 0.50%, Ni: 0.01 to 0.45%, Cr: 0.01 to 0.50%, Mo: 0.01 to 0.50%, and A Ni alloy clad steel plate having excellent low temperature toughness and HAZ toughness of the base material and excellent corrosion resistance of the clad material, the Ni alloy clad steel plate containing 0.01-0.50%, 0.005-0.080%, 0.005-0.030%, 0.0010-0.0060%, 0.070% or less of Al, 0.0010-0.0040%, and the balance being Fe and unavoidable impurities. has been disclosed.

[0006] In addition, Patent Document 2 states: "In a clad steel plate having a Ni alloy as a cladding material and a low alloy steel as a base material, the chemical components of the base material are, in mass%, C: 0.020 to 0.100%, Si: 0.10 to 0.50%, Mn: 0.75 to 1.80%, P: 0.015% or less, S: 0.0030% or less, Cu: 0.01 to 0.50%, Ni: 0.01 to 0.45%, Cr: 0.01 to 0.50%, Mo: 0.01 to 0.50%, and A Ni alloy clad steel plate having excellent low temperature toughness and HAZ toughness of the base material and excellent corrosion resistance of the clad material, the Ni alloy clad steel plate containing 0.01-0.50%, 0.005-0.080%, 0.005-0.030%, 0.0010-0.0060%, 0.070% or less of Al, 0.0010-0.0040%, and the balance being Fe and unavoidable impurities. has been disclosed.

[0007] In addition, Patent Document 3 states: "A clad steel plate having an austenitic stainless steel as a clad material and a low alloy steel as a base material, the base material being, in mass%, C: 0.020 to 0.100%, Si: 0.10 to 0.50%, Mn: 0.75 to 1.80%, P: 0.015% or less, S: 0.0030% or less, Cu: 0.01 to 0.50%, Ni: 0.01 to 0.45%, Cr: 0.01 to 0.50%, Mo: 0.01 to 0.50%, and An austenitic stainless clad steel plate having excellent low-temperature toughness and HAZ toughness of the base material and excellent corrosion resistance of the clad material, characterized in that it contains 0.01-0.50%, Nb: 0.005-0.080%, Ti: 0.005-0.030%, N: 0.0010-0.0060%, Al: 0.070% or less, Ca: 0.0010-0.0040%, with the balance being Fe and unavoidable impurities. has been disclosed.

[0008] Furthermore, Patent Document 4 states: "A clad steel plate having a base steel plate and a cladding material made of a corrosion-resistant alloy bonded to one side thereof, the base steel plate having, in mass%, C: 0.020-0.100%, Si: 0.05-0.50%, Mn: 0.75-1.80%, P: 0.015% or less, S: 0.0030% or less, Al: 0.010-0.070%, Nb: 0.005-0.080%, Ti: 0.005-0.030%, and N: 0.0010-0.0001. "A clad steel plate having a composition containing 60% Cu and the balance consisting of Fe and unavoidable impurities, the base steel plate having a steel structure in which, at a 1 / 2 position in the plate thickness direction of the base steel plate, the area ratio of bainite is 94% or more and island martensite is 6% or less, the average crystal grain size of the bainite is 25 μm or less, and further, the joint interface shear strength between the base steel plate and the clad material is 300 MPa or more." has been disclosed. [Prior art documents] [Patent documents]

[0009] [Patent Document 1] JP 2015-86422 A [Patent Document 2] JP 2015-117408 A [Patent Document 3] JP 2015-105399 A [Patent Document 4] International Publication No. 2018 / 181381 Summary of the Invention [Problem to be solved by the invention]

[0010] In the technologies described in Patent Documents 1 to 3, by applying TMCP (Thermo-mechanical control process), it is possible to improve the corrosion resistance of cladding materials, as well as the tensile strength: 535 MPa or more, DWTTSA, without compromising productivity. -20℃ It achieves mechanical properties of ≥ 85%.

[0011] Here, DWTTSA -20℃ is the ductile fracture surface area ratio obtained by a DWTT test (test temperature: -20°C) conforming to API-5L.

[0012] In the technology described in Patent Document 4, by applying DQ-T (Direct quench and tempering), the plate thickness is up to 30 mm, the tensile strength is 535 MPa or more, and the DWTTSA -30℃ It achieves mechanical properties of ≥ 85%.

[0013] However, with the above technologies, it is sometimes difficult to ensure sufficient low-temperature toughness in thick-walled materials with a plate thickness of over 30 mm. TMCP and DQ-T ensure low-temperature toughness mainly by reducing the refining of austenite through lowering the product heating temperature and by suppressing the recovery and recrystallization of austenite through lowering the rolling temperature, and then refining the crystal grains of the transformed structure after accelerated cooling. In other words, low-temperature toughness can be ensured by sufficiently refining the crystal grains of bainite. However, in order to ensure the bonding between the clad steel plate and the base material, it is important to roll at a high temperature of 1000°C or more, and since a decrease in the rolling temperature due to a decrease in the product heating temperature, etc., deteriorates the bonding property, there is a limit to the reduction in the product heating temperature and rolling temperature. In addition, as the plate thickness increases, the cooling rate of the accelerated cooling after rolling decreases, and the transformation nucleation rate of bainite decreases. Therefore, in thick clad steel plates with a plate thickness of more than 30 mm, it may be difficult to sufficiently refine the bainite grains.

[0014] The present invention has been developed in view of the above-mentioned current situation, and has a tensile strength of 535 MPa or more even if the plate thickness is more than 30 mm, and DWTTSA -30℃ The present invention aims to provide a clad steel plate having a hardness of 85% or more and excellent HAZ (Heat Affected Zone) toughness, a manufacturing method thereof, and a line pipe.

[0015] The tensile strength is determined by carrying out a tensile test in accordance with API-5L. In addition, DWTTSA -30℃ is the ductile fracture surface area ratio obtained by carrying out a DWTT test (test temperature: -30°C) in accordance with API-5L. In addition, "excellent HAZ toughness" refers to the absorbed energy vE obtained by Charpy impact testing (test temperature: -40°C) at 2 mm FL (fusion line), FL+2 mm, and FL+5 mm on the outer surface of the seam weld in accordance with DNV-OS-F101. -40℃ This means that the load is 200J or more. [Means for solving the problem]

[0016] The present inventors conducted extensive research in order to develop a clad steel plate having excellent HAZ toughness while maintaining prescribed mechanical properties even at a plate thickness exceeding 30 mm, and obtained the following findings.

[0017] (A) In order to obtain excellent low-temperature toughness, it is effective to refine the structure of the base steel plate to increase the brittle crack propagation resistance. Specifically, it is effective to make the steel structure of the base steel plate mainly composed of bainite, that is, to make the area ratio of bainite at the 1 / 2 position in the plate thickness direction of the base steel plate 80% or more and the average crystal grain size of bainite less than 20 μm.

[0018] (B) In order to achieve the above-mentioned structural control, it is important to appropriately control the chemical composition and manufacturing conditions, particularly the conditions under which the base steel sheet material and the cladding material are laminated together to form a slab, which is then rolled and reheated, quenched and tempered.

[0019] As mentioned above, in order to sufficiently refine the grains of the transformed structure in thick clad steel plates with a plate thickness of over 30 mm, it is important to properly control the chemical composition and manufacturing conditions, especially the conditions for the reheating, quenching, and tempering treatment. In this regard, the reheating, quenching, and tempering treatment makes it difficult to utilize precipitation strengthening such as Nb, and a large amount of alloying elements must be added to ensure tensile strength compared to TMCP and DQ-T. As a result, island martensite is easily formed in the HAZ, making it difficult to ensure HAZ toughness.

[0020] Therefore, in order to achieve both tensile strength and HAZ toughness, the inventors conducted further research and discovered that by properly controlling the content of alloying elements, more specifically, by adjusting the component composition to mainly satisfy the following formulas (1), (2), (3), and (4), it is possible to achieve excellent HAZ toughness while ensuring predetermined mechanical properties, even in plate thicknesses exceeding 30 mm.

[0021] 0.40≦Ceq≦0.50 (1) Here, Ceq is defined by the following equation. Ceq=[C]+[Mn] / 6+([Cu]+[Ni]) / 15+([Cr]+[Mo]+[V]) / 5 Additionally, [C], [Si], [Mn], [Cu], [Ni], [Cr], [Mo], [Nb] and [V] are the contents (mass%) of C, Si, Mn, Cu, Ni, Cr, Mo, Nb and V in the base steel plate, respectively. 0.030≦[C]≦0.060 (2) [Si]<0.10 (3) 0.005≦[Nb]≦0.060 (4)

[0022] The present invention was completed based on the above findings and as a result of further investigation. That is, the gist and configuration of the present invention are as follows.

[0023] [1] A clad steel plate in which a clad material is bonded to one or both sides of a base steel plate, The base steel sheet is, in mass%, C: 0.030% or more and 0.060% or less, Si: less than 0.10% Mn: 1.00% or more and 1.80% or less, P: 0.015% or less, S: 0.003% or less, Al: 0.010% or more and 0.070% or less, Nb: 0.005% or more and 0.060% or less, Ti: 0.005% or more and 0.030% or less, N: 0.0010% or more and 0.0060% or less and further comprising Cu: 0.01% or more and 0.50% or less, Ni: 0.01% or more and 0.50% or less, Cr: 0.01% or more and 0.50% or less, Mo: 0.01% or more and 0.50% or less, V: 0.001% to 0.100% and Ca: 0.0005% or more and 0.0040% or less and containing one or more selected from the following: The relationship of the following formula (1) is satisfied, The balance is Fe and unavoidable impurities. Moreover, the base steel sheet is A clad steel plate having a steel structure in which, at a 1 / 2 position in the plate thickness direction of the base steel plate, there is 80% or more bainite by area ratio, and the average crystal grain size of the bainite is less than 20 μm. Note 0.40≦Ceq≦0.50 (1) Here, Ceq is defined by the following equation. Ceq=[C]+[Mn] / 6+([Cu]+[Ni]) / 15+([Cr]+[Mo]+[V]) / 5 Additionally, [C], [Mn], [Cu], [Ni], [Cr], [Mo] and [V] are the contents (mass%) of C, Mn, Cu, Ni, Cr, Mo and V in the base steel plate, respectively. [2] The clad steel plate according to [1], wherein the clad material is a Ni-based alloy or an austenitic stainless steel. [3] A hot rolling process in which a slab formed by stacking at least one set of a material having the composition of the base steel plate described in [1] and a material of a clad material is hot rolled to obtain a rolled plate containing the base steel plate and the clad material; Next, the rolled plate is heated to a temperature of Ac 3 Heat to 1000°C or higher, and after heating, cool down to Ar at the surface temperature. 3 a quenching process in which the base steel plate is cooled to a temperature of 500°C or higher, an average cooling rate of 5°C / s or higher, and a cooling stop temperature of 500°C or lower at a temperature at a 1 / 2 position in the thickness direction of the base steel plate; The method for manufacturing a clad steel plate further includes a tempering treatment step of tempering the rolled plate at a temperature at 1 / 2 the thickness direction of the base steel plate in a temperature range of 350°C or higher and 650°C or lower. [4] A method for manufacturing clad steel plate described in [3] above, in which the slab is laminated in the following order: base steel plate material, clad material material, clad material material, and base steel plate material. [5] A line pipe using the clad steel plate according to [1] or [2] above. Effect of the Invention

[0024] According to the present invention, even if the plate thickness exceeds 30 mm, the tensile strength is secured to be 535 MPa or more, and the DWTTSA -30℃ Therefore, the clad steel plate having excellent HAZ toughness can be obtained. Furthermore, the above-mentioned clad steel plate is extremely useful industrially since it can be applied to line pipes for transporting oil and natural gas, which are exposed to severe corrosive environments. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0025] The present invention will be specifically described below.

[0026] The present invention is directed to a clad steel plate in which a clad material is bonded to one or both sides of a base steel plate. The thickness of the clad steel plate is not particularly limited, but may be more than 30 mm. The thickness of the clad steel plate may be 45 mm or less. The thickness of the clad steel plate is the total thickness of the base steel plate and the clad material. The thickness of the base steel plate may be 5 to 42 mm, and the thickness of the cladding material may be 1.5 to 4.0 mm.

[0027] First, the composition of the base steel plate in the clad steel plate of the present invention will be described. Note that the unit of the composition is always "mass %", but hereinafter, unless otherwise specified, it will be simply indicated as "%".

[0028] 1. Composition of base steel sheet C: 0.030% or more and 0.060% or less C is an element that contributes to precipitation strengthening as a carbide. If the C content is less than 0.030%, sufficient strength cannot be ensured. On the other hand, if the C content exceeds 0.060%, the toughness of the base steel plate and the HAZ toughness are deteriorated. Therefore, the C content is set to 0.030% or more and 0.060% or less. The C content is preferably 0.030% or more and less than 0.050%.

[0029] Silicon: Less than 0.10% Since Si does not dissolve in cementite, it delays the formation of cementite, promotes the formation of island martensite, and delays the decomposition, thereby deteriorating HAZ toughness. Therefore, the Si content is set to less than 0.10%. The Si content is preferably 0.08% or less. The lower limit of the Si content is not particularly limited, and may be 0%.

[0030] Mn: 1.00% or more and 1.80% or less Mn is an element added to ensure strength and toughness. If the Mn content is less than 1.00%, the effect is insufficient. On the other hand, if the Mn content exceeds 1.80%, the weldability deteriorates. Therefore, the Mn content is set to 1.00% or more and 1.80% or less. The Mn content is preferably 1.30% or more.

[0031] P:0.015% or less P deteriorates weldability. Therefore, the P content is set to 0.015% or less, and preferably 0.010% or less. The lower limit of the P content is not particularly limited, and may be 0%.

[0032] S: 0.003% or less S is generally present in steel as sulfide-based inclusions and deteriorates ductility and toughness. Therefore, it is preferable to reduce S as much as possible, and the S content is set to 0.003% or less, and preferably 0.001% or less. There is no particular lower limit for the S content, and it may be 0%.

[0033] Al: 0.010% or more and 0.070% or less Al is added for deoxidation, but if the Al content is less than 0.010%, the effect is insufficient. On the other hand, if the Al content exceeds 0.070%, alumina clusters are formed, which deteriorates ductility. Therefore, the Al content is set to 0.010% or more and 0.070% or less. The Al content is preferably 0.010% or more and 0.040% or less.

[0034] Nb: 0.005% or more and 0.060% or less Nb is effective in increasing the strength of the base steel plate by precipitation strengthening and increasing hardenability. In addition, the pinning effect of carbonitride formation suppresses the coarsening of austenite, contributing to improving the toughness of the base steel plate. However, if the Nb content is less than 0.005%, the effect is insufficient. On the other hand, if the Nb content exceeds 0.060%, island martensite and coarse Nb carbonitrides are generated, deteriorating the HAZ toughness. Therefore, the Nb content is set to 0.005% or more and 0.060% or less. The Nb content is preferably 0.010% or more. Moreover, the Nb content is preferably 0.040% or less.

[0035] Ti: 0.005% or more and 0.030% or less When Ti is contained at 0.005% or more, the pinning effect caused by nitride formation suppresses the coarsening of austenite, and contributes to ensuring the toughness of the base steel plate and the toughness of the HAZ. However, when the Ti content exceeds 0.030%, the nitrides become coarse and become the starting point of brittle fracture or ductile fracture. Therefore, the Ti content is set to 0.005% or more and 0.030% or less. The Ti content is preferably 0.020% or less.

[0036] N: 0.0010% or more and 0.0060% or less When N is contained at 0.0010% or more, the pinning effect caused by nitride formation suppresses the coarsening of austenite, and contributes to ensuring the toughness of the base steel plate and the HAZ toughness. However, if the N content exceeds 0.0060%, the HAZ toughness deteriorates. Therefore, the N content is set to 0.0010% or more and 0.0060% or less. The N content is preferably 0.0020% or more. In addition, the N content is preferably 0.0050% or less.

[0037] In order to fully utilize the pinning effect due to nitride formation, it is preferable to adjust the ratio of Ti content to N content. Specifically, when the Ti content / N content ratio is less than 2.0 or exceeds 3.5 in mass%, the pinning effect due to nitride formation is not fully utilized, and austenite may become coarse, resulting in deterioration of HAZ toughness. Therefore, it is preferable to set the Ti content / N content ratio to 2.0 or more. It is also preferable to set the Ti content / N content ratio to 3.5 or less.

[0038] One or more selected from Cu: 0.01% or more and 0.50% or less, Ni: 0.01% or more and 0.50% or less, Cr: 0.01% or more and 0.50% or less, Mo: 0.01% or more and 0.50% or less, V: 0.001% or more and 0.100% or less, and Ca: 0.0005% or more and 0.0040% or less Cu, Ni, Cr, and Mo are all elements that improve hardenability and contribute to increasing the strength of the base steel sheet. V also contributes to increasing the strength of the base steel sheet by precipitation strengthening. In order to obtain such effects, when one or more of Cu, Ni, Cr, Mo, and V are contained, Cu, Ni, Cr, and Mo are each 0.01% or more, and V is 0.001% or more. Cu, Ni, Cr, and Mo are each preferably 0.05% or more. V is preferably 0.010% or more.

[0039] On the other hand, if the Cu, Cr and Mo contents exceed 0.50%, the HAZ toughness may be deteriorated. Therefore, when Cu, Cr and Mo are contained, their contents are each set to 0.50% or less. Cu, Cr and Mo are preferably set to 0.40% or less.

[0040] Furthermore, when the V content exceeds 0.100%, the HAZ toughness may be deteriorated, so when V is contained, the V content is set to 0.100% or less.

[0041] Furthermore, since Ni is an expensive element, the inclusion of a large amount of Ni leads to an increase in costs. Therefore, when Ni is included, the content is set to 0.50% or less, and preferably 0.40% or less.

[0042] Ca has the function of fixing S in steel and improving the toughness of the base steel plate. To obtain this effect, Ca is contained in an amount of 0.0005% or more. However, if the Ca content exceeds 0.0040%, the amount of inclusions in the steel increases, and the toughness of the base steel plate and the HAZ toughness may deteriorate. Therefore, when Ca is contained, the Ca content is set to 0.0005% or more and 0.0040% or less. The Ca content is preferably 0.0010% or more. Moreover, the Ca content is preferably 0.0030% or less.

[0043] The fundamental components have been described above, but the value of Ceq is further appropriately controlled as shown in the following formula (1). 0.40≦Ceq≦0.50 (1) Here, Ceq is defined by the following equation. Ceq=[C]+[Mn] / 6+([Cu]+[Ni]) / 15+([Cr]+[Mo]+[V]) / 5 Additionally, [C], [Mn], [Cu], [Ni], [Cr], [Mo] and [V] are the contents (mass%) of C, Mn, Cu, Ni, Cr, Mo and V in the base steel plate, respectively.

[0044] 0.40≦Ceq≦0.50 Ceq is a value that serves as an index of the hardness of the HAZ, but also serves as an index of the strength of the base steel plate. Here, if the value of Ceq is less than 0.40, sufficient strength of the base steel plate cannot be ensured. On the other hand, if the value of Ceq exceeds 0.50, the toughness of the base steel plate and the HAZ toughness are deteriorated. Therefore, Ceq is set to 0.40 or more and 0.50 or less. Ceq is preferably 0.40 or more and 0.48 or less.

[0045] The components other than those mentioned above are Fe and unavoidable impurities. That is, the base steel plate contains, by mass%, C: 0.030% or more and 0.060% or less, Si: less than 0.10%, Mn: 1.00% or more and 1.80% or less, P: 0.015% or less, S: 0.003% or less, Al: 0.010% or more and 0.070% or less, Nb: 0.005% or more and 0.060% or less, Ti: 0.005% or more and 0.030% or less, and N: 0.0010% or more and 0.0060% or less, Furthermore, it contains one or more selected from Cu: 0.01% or more and 0.50% or less, Ni: 0.01% or more and 0.50% or less, Cr: 0.01% or more and 0.50% or less, Mo: 0.01% or more and 0.50% or less, V: 0.001% or more and 0.100% or less, and Ca: 0.0005% or more and 0.0040% or less, It has a composition that satisfies the relationship of the above formula (1), with the balance being Fe and unavoidable impurities.

[0046] 2. Microstructure of base steel plate The base steel plate has a steel structure in which bainite accounts for 80% or more in area ratio at a 1 / 2 position in the plate thickness direction of the base steel plate, and the average crystal grain size of the bainite is less than 20 μm.

[0047] Area ratio of bainite at 1 / 2 position in the thickness direction of the base steel plate: 80% or more Bainite is an important structure for achieving both strength and low-temperature toughness. Bainite also effectively contributes to improving the strength of steel plate by strengthening the transformation structure. For this reason, the steel structure of the base steel plate needs to be a structure mainly composed of bainite, and specifically, the area ratio of bainite to the entire steel structure at the 1 / 2 position in the plate thickness direction of the base steel plate (hereinafter simply referred to as the 1 / 2 position) needs to be 80% or more. The area ratio of bainite is preferably 85% or more. The area ratio of bainite may be 100%.

[0048] As described above, the steel structure of the base steel plate must be basically composed of the above-mentioned bainite, but it may contain trace amounts of island martensite, ferrite, and cementite as remaining structures other than bainite, and this is acceptable as long as the total area ratio of these remaining structures is 20% or less. The area ratio of the remaining structure may be 0%. If the remaining structure exceeds 20%, the area ratio of bainite becomes small, making it impossible to achieve both strength and low-temperature toughness.

[0049] Here, the area ratio of each phase at the 1 / 2 sheet thickness position was determined as follows. That is, the L-section (a section parallel to the rolling direction and parallel to the normal direction of the rolling surface) at 1 / 2 the thickness of the base steel plate in the plate thickness direction was mirror polished. Then, to identify the island martensite, the base steel plate was corroded by electrolytic etching (electrolyte: 100 ml distilled water + 25 g sodium hydroxide + 5 g picric acid). To identify other structures, the base steel plate was corroded using nital as an etching solution. Then, a scanning electron microscope (SEM) was used to examine randomly selected 1.2 × 10 -2 mm 2 The area is observed and the area ratio is calculated by image analysis.

[0050] Average grain size of bainite: less than 20μm Since the grain boundaries of bainite act as resistance to the propagation of brittle cracks, the refinement of the grains contributes to the improvement of low-temperature toughness. Therefore, the average grain size of bainite is set to less than 20 μm. Although there is no particular lower limit, the average grain size of bainite is preferably set to 5 μm or more.

[0051] Here, the average grain size of bainite is determined as follows. That is, the L cross section (a cross section parallel to the rolling direction and parallel to the normal direction of the rolling surface) at the 1 / 2 position in the thickness direction of the base steel plate was mirror-polished, and then 1.2 × 10 -2 mm 2The crystal orientation of this region was measured, and regions where the angle difference between adjacent pixels was 15° or more were determined to be grain boundaries through image analysis. The average grain size d area (μm) is the area occupied by each grain a i (μm 2 ) and the equivalent circle diameter d of each grain i The value was calculated using the following formula: d area =Σ(a i d i ) / Σa i

[0052] 3. Cladding material In the clad steel plate of the present invention, a cladding material is bonded to one or both sides of a base steel plate. The cladding material is preferably made of a corrosion-resistant alloy.

[0053] The cladding material is not particularly limited, but examples thereof include Ni-based alloys and austenitic stainless steel. In particular, Ni-based alloys are preferable because they exhibit high stress corrosion cracking resistance in environments with high hydrogen sulfide partial pressures (sour environments).

[0054] The Ni-based alloy is, for example, Alloy 625 or Alloy 825, and from the viewpoint of stress corrosion cracking resistance, Alloy 625 is particularly preferable.

[0055] Here, Alloy625 is a Ni-based alloy equivalent to NCF625 of JIS G 4902, and among these, a Ni-based alloy having a component composition containing, in mass%, C: 0.030% or less, Si: 0.02 to 0.50%, Mn: 0.02 to 0.50%, P: 0.015% or less, S: 0.015% or less, Cr: 20.0 to 23.0%, Mo: 8.0 to 10.0%, Fe: 5.0% or less, Al: 0.02 to 0.40%, Ti: 0.10 to 0.40%, the total amount of Nb and Ta: 3.15 to 4.15%, and the balance being Ni and unavoidable impurities is preferable.

[0056] Moreover, Alloy825 is a Ni-based alloy equivalent to NCF825 of JIS G 4902, and among them, a Ni-based alloy having a component composition containing, in mass%, C: 0.020% or less, Si: 0.50% or less, Mn: 1.00% or less, P: 0.030% or less, S: 0.0050% or less, Cu: 1.50 to 3.00%, Ni: 38.0 to 46.0%, Cr: 19.5 to 23.5%, Mo: 2.50 to 3.50%, Al: 0.01 to 0.20%, Ti: 0.60 to 1.20%, with the balance being Fe and unavoidable impurities is preferable. The following describes the preferred compositions of the above-mentioned Alloy 625 and Alloy 825. Note that the unit of the composition is always "mass %", but hereinafter, unless otherwise specified, it will simply be represented as "%".

[0057] (1) Optimal composition of Alloy 625 C: 0.030% or less C is an element that precipitates as carbides at grain boundaries during the thermal history during the manufacture of clad steel plate, degrading corrosion resistance. Therefore, the C content is preferably 0.030% or less, and more preferably 0.020% or less. The lower limit of the C content is not particularly limited and may be 0%.

[0058] Silicon: 0.02 to 0.50% Silicon is added for deoxidation. If the silicon content is less than 0.02%, the effect is insufficient. On the other hand, if the silicon content exceeds 0.50%, the corrosion resistance is deteriorated. Therefore, the silicon content is preferably 0.02 to 0.50%, and more preferably 0.02 to 0.20%.

[0059] Mn: 0.02 to 0.50% Mn is added for deoxidation. If the Mn content is less than 0.02%, the effect is insufficient. On the other hand, if the Mn content exceeds 0.50%, the corrosion resistance is deteriorated. Therefore, the Mn content is preferably 0.02 to 0.50%, and more preferably 0.02 to 0.15%.

[0060] P:0.015% or less P is an impurity element that segregates at grain boundaries and deteriorates corrosion resistance. Therefore, the P content is preferably 0.015% or less, and more preferably 0.010% or less. The lower limit of the P content is not particularly limited, and may be 0%.

[0061] S: 0.015% or less Like P, S is an impurity element that segregates to grain boundaries and deteriorates corrosion resistance. Therefore, the S content is preferably 0.015% or less, and more preferably 0.0010% or less. The lower limit of the S content is not particularly limited, and may be 0%.

[0062] Cr: 20.0~23.0% Cr forms a highly protective oxide film on the surface of the metal, improving pitting corrosion resistance and intergranular corrosion resistance. In addition, Cr improves stress corrosion cracking resistance in a sour environment when added in combination with Ni. However, the Cr content must be determined while taking into consideration the balance with Ni and other alloys. From this perspective, the Cr content is preferably 20.0-23.0%, and more preferably 21.5-23.0%.

[0063] Mo: 8.0-10.0% Mo improves pitting corrosion resistance and crevice corrosion resistance. In addition, Mo improves stress corrosion cracking resistance in a sour environment when added in combination with Ni. However, the Mo content must be considered in terms of its balance with Ni and other alloys. From this perspective, the Mo content is preferably 8.0-10.0%, and more preferably 8.5-10.0%.

[0064] Fe:5.0% or less Fe is an impurity that is inevitably mixed in when ferrochromium, ferromolybdenum, or the like is used as a raw material, and if the Fe content exceeds 5.0%, the corrosion resistance deteriorates. Therefore, the Fe content is preferably 5.0% or less, and more preferably 3.5% or less. The lower limit of the Fe content is not particularly limited, and may be 0%.

[0065] Al: 0.02 to 0.40% Al is an effective deoxidizing element, but if the Al content is less than 0.02%, the effect is insufficient. However, if the Al content exceeds 0.40%, the stress corrosion cracking resistance is deteriorated. Therefore, the Al content is preferably 0.02 to 0.40%, and more preferably 0.02 to 0.25%.

[0066] Ti: 0.10-0.40% Ti is effective in fixing C. If the Ti content is less than 0.10%, the fixation of C becomes incomplete, and carbides that deteriorate corrosion resistance are precipitated. However, if the Ti content exceeds 0.40%, Ti is precipitated as an intermetallic compound, which deteriorates the bondability with the base steel sheet. Therefore, the Ti content is preferably 0.10 to 0.40%, and more preferably 0.10 to 0.30%.

[0067] Total amount of Nb and Ta: 3.15~4.15% Both Nb and Ta are effective in fixing C. If the total amount (total content) of Nb and Ta is less than 3.15%, the effect is insufficient. On the other hand, if the total amount of Nb and Ta exceeds 4.15%, Nb and Ta form a low melting point intermetallic compound, which reduces hot workability. Therefore, the total amount of Nb and Ta is preferably 3.15 to 4.15%.

[0068] The other components are Ni and unavoidable impurities. Ni is an element that improves corrosion resistance, and in particular, it significantly improves stress corrosion cracking resistance in a sawdust environment. For this reason, the Ni content is preferably 58% or more.

[0069] (2) Optimal composition of Alloy 825 C: 0.020% or less C is an element that precipitates as carbides at grain boundaries during the thermal history during the manufacture of clad steel plate, and deteriorates corrosion resistance. Therefore, the C content is preferably 0.020% or less, and more preferably 0.015% or less. The lower limit of the C content is not particularly limited, and may be 0%.

[0070] Si:0.50% or less If the Si content exceeds 0.50%, Si remains as a nonmetallic inclusion, which deteriorates the corrosion resistance. Therefore, the Si content is preferably 0.50% or less, and more preferably 0.30% or less. There is no particular lower limit for the Si content, but from the viewpoint of obtaining a sufficient deoxidizing effect, it is preferably 0.02% or more.

[0071] Mn: 1.00% or less If the Mn content exceeds 1.00%, the corrosion resistance is deteriorated. Therefore, the Mn content is preferably 1.00% or less, and more preferably 0.50% or less. Although there is no particular restriction on the lower limit of the Mn content, it is preferably 0.02% or more from the viewpoint of obtaining a sufficient deoxidizing effect.

[0072] P:0.030% or less P is an impurity element that segregates at grain boundaries and deteriorates corrosion resistance. Therefore, the P content is preferably 0.030% or less, and more preferably 0.020% or less. The lower limit of the P content is not particularly limited, and may be 0%.

[0073] S: 0.0050% or less Like P, S is an impurity element that segregates to grain boundaries and deteriorates corrosion resistance. Therefore, the S content is preferably 0.0050% or less, and more preferably 0.0010% or less. The lower limit of the S content is not particularly limited, and may be 0%.

[0074] Cu: 1.50-3.00% Cu is an element effective in improving corrosion resistance in a sulfuric acid environment. However, if the Cu content is less than 1.50%, the effect is insufficient. On the other hand, if the Cu content exceeds 3.00%, the effect is saturated. Therefore, the Cu content is preferably 1.50 to 3.00%, and more preferably 1.80 to 3.00%.

[0075] Ni: 38.0~46.0% Ni is an element that improves corrosion resistance, and in particular significantly improves stress corrosion cracking resistance in a sawmill environment. However, Ni is a very expensive element, and adding a large amount of Ni increases costs. For this reason, the Ni content must be determined by considering the balance between the effect of improving corrosion resistance and costs. From this perspective, the Ni content is preferably 38.0 to 46.0%.

[0076] Cr: 19.5~23.5% Cr forms a highly protective oxide film on the surface of the metal, improving pitting corrosion resistance and intergranular corrosion resistance. In addition, Cr improves stress corrosion cracking resistance in a sour environment when added in combination with Ni. However, the Cr content must be determined while taking into consideration the balance with Ni and other alloys. From this perspective, the Cr content is preferably 19.5-23.5%, and more preferably 21.5-23.5%.

[0077] Mo: 2.50-3.50% Mo improves pitting corrosion resistance and crevice corrosion resistance. In addition, Mo improves stress corrosion cracking resistance in a sawdust environment when added in combination with Ni. However, the Mo content must be considered in terms of its balance with Ni and other alloys. From this viewpoint, the Mo content is preferably 2.50-3.50%, and more preferably 3.00-3.50%.

[0078] Al: 0.01 to 0.20% Al is an effective deoxidizing element. However, if the Al content is less than 0.01%, the effect is insufficient. On the other hand, if the Al content exceeds 0.20%, the stress corrosion cracking resistance is deteriorated. Therefore, the Al content is preferably 0.01 to 0.20%, more preferably 0.10% or more, and more preferably 0.15% or less.

[0079] Ti: 0.60-1.20% Ti is effective in fixing C. If the Ti content is less than 0.60%, the fixation of C becomes incomplete, and carbides that deteriorate corrosion resistance are precipitated. However, if the Ti content exceeds 1.20%, Ti is precipitated as an intermetallic compound, which deteriorates the bondability with the base steel sheet. Therefore, the Ti content is preferably 0.60 to 1.20%, and more preferably 0.65 to 1.20%.

[0080] The components other than those mentioned above are Fe and unavoidable impurities.

[0081] The preferred component compositions of Alloy 625 and Alloy 825 have been explained above, but examples of corrosion-resistant alloys other than Ni-based alloys include austenitic stainless steels.

[0082] Here, the austenitic stainless steel refers to, for example, austenitic stainless steel as defined by JIS, and examples thereof include SUS304, SUS316, SUS304L, and SUS316L.

[0083] Furthermore, among austenitic stainless steels, it is preferable that the stainless steel have a composition containing, by mass%, C: 0.030% or less, Si: 1.00% or less, Mn: 2.00% or less, P: 0.045% or less, S: 0.030% or less, Ni: 12.00 to 15.00%, Cr: 16.00 to 18.00%, Mo: 2.00 to 3.00%, with the balance being Fe and unavoidable impurities.

[0084] The following describes the preferred composition of the above-mentioned austenitic stainless steel. Note that the unit of composition is always "mass %", but hereinafter, unless otherwise specified, it will be simply represented as "%".

[0085] (3) Suitable chemical composition of austenitic stainless steel C: 0.030% or less C is an element that precipitates as carbides at grain boundaries during the thermal history during the manufacture of clad steel plate, and deteriorates corrosion resistance. Therefore, the C content is preferably 0.030% or less. More preferably, it is 0.020% or less. Further preferably, it is 0.015% or less. The lower limit of the C content is not particularly limited, and may be 0%.

[0086] Si: 1.00% or less If the Si content exceeds 1.00%, Si remains as a nonmetallic inclusion and deteriorates the corrosion resistance. Therefore, the Si content is preferably 1.00% or less, and more preferably 0.75% or less. The lower limit of the Si content is not particularly limited, and may be 0%.

[0087] Mn: 2.00% or less If the Mn content exceeds 2.00%, the corrosion resistance is deteriorated. Therefore, the Mn content is preferably 2.00% or less. More preferably, it is 1.40% or less. Further preferably, it is 1.00% or less. The lower limit of the Mn content is not particularly limited, and may be 0%.

[0088] P:0.045% or less P is an impurity element that segregates at grain boundaries and deteriorates corrosion resistance. Therefore, the P content is preferably 0.045% or less, and more preferably 0.030% or less. The lower limit of the P content is not particularly limited, and may be 0%.

[0089] S: 0.030% or less Like P, S is an impurity element that segregates to grain boundaries and deteriorates corrosion resistance. Therefore, the S content is preferably 0.030% or less. More preferably, it is 0.010% or less. The S content is further preferably 0.001% or less. The lower limit of the S content is not particularly limited and may be 0%.

[0090] Ni: 12.00~15.00% Ni is an element that improves corrosion resistance, and particularly significantly improves stress corrosion cracking resistance in a sawdust environment. However, Ni is a very expensive element, and adding a large amount of Ni leads to increased costs. For this reason, the Ni content must be determined by considering the balance between the effect of improving corrosion resistance and costs, and from this perspective, the Ni content is preferably 12.00 to 15.00%. The Ni content is more preferably 12.50% or more. Moreover, the Ni content is more preferably 14.50% or less.

[0091] Cr: 16.00~18.00% Cr forms a highly protective oxide film on the surface of the metal, improving pitting corrosion resistance and intergranular corrosion resistance. In addition, Cr improves stress corrosion cracking resistance in a sour environment when added in combination with Ni. However, the Cr content must be determined while taking into consideration the balance with Ni and other alloys. From this viewpoint, the Cr content is preferably 16.00 to 18.00%. The Cr content is more preferably 16.50% or more. The Cr content is more preferably 17.50% or less.

[0092] Mo: 2.00-3.00% Mo improves pitting corrosion resistance and crevice corrosion resistance. In addition, Mo improves stress corrosion cracking resistance in a sawdust environment when added in combination with Ni. However, the Mo content must be considered in terms of its balance with Ni and other alloys. From this viewpoint, the Mo content is preferably 2.00-3.00%. The Mo content is more preferably 2.20% or more. The Mo content is more preferably 2.80% or less.

[0093] The components other than those mentioned above are Fe and unavoidable impurities.

[0094] 4. Manufacturing method Next, a method for producing the clad steel plate of the present invention will be described. A method for producing a clad steel plate according to one embodiment of the present invention includes the steps of: A hot rolling process in which at least one set of a material having the component composition of the base steel plate and a material of the clad material is laminated and hot rolled to a slab to obtain a rolled plate containing the base steel plate and the clad material; Next, the rolled plate is heated to a temperature of Ac at a position 1 / 2 the thickness of the base steel plate in the thickness direction. 3 Heat to 1000°C or higher, and after heating, cool down to Ar at the surface temperature. 3 a quenching process in which the base steel plate is cooled to a temperature of 500°C or lower at an average cooling rate of 5°C / s or higher and a cooling stop temperature of 500°C or lower at a temperature at a half-thickness position in the thickness direction of the base steel plate; The method further includes a tempering step of tempering the rolled sheet at a temperature at 1 / 2 the thickness direction of the base steel sheet in a temperature range of 350°C to 650°C.

[0095] Here, the slab is formed by stacking the base steel plate material and the cladding material material in the order of, for example, (a) the base steel plate material, the cladding material material (base steel plate material / cladding material material), or (b) the base steel plate material, the cladding material material, the cladding material material, and the base steel plate material (base steel plate material / cladding material material / cladding material material / base steel plate material), and then annealing the base steel plate material in a vacuum (negative pressure) environment, specifically, for 10 -4 The base steel plate and the cladding material are temporarily attached by electron beam welding or laser beam welding in an environment with a pressure of less than torr.

[0096] In addition, when using a slab in the form of (b), a release material is applied in advance between the cladding material materials, and after the tempering process is completed, the upper and lower parts are peeled off to obtain a clad steel plate in which the cladding material is bonded to one side of the base steel plate that will become the product plate.

[0097] Hot rolling The slab is subjected to hot rolling to obtain a rolled plate consisting of the base steel plate and the clad material. Although the hot rolling conditions are not particularly limited, in terms of ensuring the bonding between the clad material and the base material, when Alloy625 is used as the clad material, it is preferable to perform hot rolling with a reduction ratio of 2.0 or more in a temperature range with a surface temperature of 950°C or more. However, when a Ni-based alloy such as Alloy825 or an austenitic stainless steel is used as the clad material, it is preferable to perform hot rolling with a reduction ratio of 1.5 or more in a temperature range with a surface temperature of 950°C or more. The reduction ratio in a temperature range with a surface temperature of 950°C or more is [the plate thickness of the slab before hot rolling]÷[the plate thickness of the slab after rolling in a temperature range with a surface temperature of 950°C or more].

[0098] Quenching Treatment In the quenching process, the above-mentioned rolled plate is heated to a temperature of Ac at a position half the thickness of the base steel plate in the thickness direction. 3 Heat to 1000°C or higher, and after heating, cool down to Ar at the surface temperature. 3 Cooling is performed to a temperature of 500°C or higher, an average cooling rate of 5°C / s or higher, and a cooling stop temperature of 500°C or lower at the 1 / 2 position in the thickness direction of the base steel plate.

[0099] Heating temperature: AC 3 Temperature above 1000℃ below Heating temperature is Ac 3 If the heating temperature is below this temperature, the austenite transformation will not be completed, the final structure will be non-uniform, and the toughness of the base steel plate will deteriorate. On the other hand, if the heating temperature exceeds 1000°C, the austenite will coarsen due to the dissolution of Nb carbonitrides that act on the pinning of austenite, and the toughness of the base steel plate will deteriorate. Therefore, the heating temperature should be set to Ac 3 The temperature is set to 1000°C or higher, preferably 900 to 1000°C. 3 The transformation point can be calculated by the following formula. Ac 3 (℃) = 912.0-230.5 x C + 31.6 x Si-20.4 x Mn-39.8 x Cu-18.1 x Ni-14.8 x Cr + 16.8 x Mo Here, the element symbols in the above formula indicate the content (mass%) of each element in the base steel plate portion of the rolled plate, and are set to zero when the element is not contained. The heating temperature referred to here is the temperature at a 1 / 2 position in the thickness direction of the base steel plate portion of the rolled plate.

[0100] Cooling start temperature: Ar at surface temperature 3 above temperature The cooling start temperature is the surface temperature and Ar 3 If the cooling start temperature is less than this temperature, ferrite will form in the base steel sheet prior to bainite transformation, making it difficult to achieve the desired strength. Therefore, the cooling start temperature is set to the surface temperature of the rolled sheet and Ar 3 The upper limit is not particularly limited, but it is preferably 1000°C or lower. 3 The temperature can be calculated according to the following formula: Ar 3 (℃) = 910-310 x C-80 x Mn-20 x Cu-15 x Cr-55 x Ni-80 x Mo Here, the element symbols in the above formula indicate the content (mass%) of each element in the base steel plate portion of the rolled plate, and are set to zero when the element is not contained.

[0101] Average cooling rate: 5℃ / s or more If the average cooling rate is less than 5°C / s, the crystal grains of the transformed structure of the base steel plate become coarse, and the toughness deteriorates. In addition, it becomes difficult to ensure the target strength. Therefore, the average cooling rate is set to 5°C / s or more. Although there is no particular upper limit, the average cooling rate is preferably set to 50°C / s or less. The average cooling rate referred to here is calculated by dividing the difference (°C) between the cooling start temperature (°C) and the cooling stop temperature (°C) at the 1 / 2 position in the thickness direction of the base steel plate portion of the rolled plate by the cooling time (s).

[0102] Cooling stop temperature: 500℃ or less If the cooling stop temperature exceeds 500°C, structures that adversely affect the toughness and Charpy absorbed energy, such as coarse cementite and island martensite, are generated in the base steel plate. Therefore, the cooling stop temperature is set to 500°C or less. The cooling stop temperature is preferably 300°C or less. Although there is no particular limit to the lower limit, the cooling stop temperature is preferably 25°C or more. The cooling stop temperature referred to here is the temperature at the 1 / 2 position in the thickness direction of the base steel plate portion of the rolled plate.

[0103] Tempering Treatment Tempering temperature: 350℃ or higher and 650℃ or lower After the above quenching treatment, the rolled plate is heated and tempered. If the tempering temperature is less than 350°C, the decomposition of island martensite and the recovery of dislocations, which have a negative effect on the toughness of the base steel plate, are not sufficient, and the toughness of the base steel plate is deteriorated. On the other hand, if the tempering temperature exceeds 650°C, precipitates such as cementite become coarse, and the toughness of the base steel plate is deteriorated. In addition, the formation of precipitates may deteriorate the corrosion resistance of the cladding material. Therefore, the tempering temperature is set to 350°C or more and 650°C or less. The tempering temperature is preferably 400° C. or higher. In addition, the tempering temperature is preferably 600° C. or lower, and more preferably 550° C. or lower. The tempering temperature referred to here is the temperature at a 1 / 2 position in the thickness direction of the base steel plate of the rolled plate. The holding time at the tempering temperature is preferably 5 minutes or more and 60 minutes or less from the viewpoints of decomposition of island martensite, recovery of dislocations, and formation and coarsening of precipitates. EXAMPLES

[0104] The composite of the base steel plate material having the composition shown in Table 1 (the balance is Fe and unavoidable impurities) and the Ni-based alloy (Alloy625) having the composition shown in Table 2 (the balance is Ni and unavoidable impurities), or the Ni-based alloy (Alloy825) having the composition shown in Table 3 (the balance is Fe and unavoidable impurities), or the austenitic stainless steel (SUS316L) having the composition shown in Table 4 (the balance is Fe and unavoidable impurities) The slabs were laminated in the order of (a) base steel plate material / clad material material, or (b) base steel plate material / clad material / clad material / base steel plate material, and hot-rolled to form a rolled plate consisting of the base steel plate and clad material. The rolled plate obtained was then quenched and tempered under the conditions shown in Table 5 to produce a clad steel plate (base steel plate thickness: 30 mm, clad material thickness: 3 mm) with a plate thickness of 33 mm in total for the base steel plate and clad material. Of the slabs laminated in the order of (a) base steel plate material / clad material material and (b) base steel plate material / clad material / clad material / base steel plate material, Nos. 21 to 24 adopted (a), and the others adopted (b).

[0105] [Table 1]

[0106] [Table 2]

[0107] [Table 3]

[0108] [Table 4]

[0109] [Table 5]

[0110] The thus obtained clad steel plate was subjected to a tensile test and a DWTT test (test temperature: -30°C) in accordance with API-5L, and the tensile strength, yield strength, and ductile fracture surface ratio: DWTTSA -30℃ In addition, seam welded joints were fabricated and Charpy impact tests (test temperature: -40°C) were performed at FL, FL+2mm, and FL+5mm from the outer surface of the seam weld in accordance with DNV-OS-F101. The absorbed energy: vE -40℃ asked for.

[0111] Tensile strength, ductile fracture surface area ratio: DWTTSA -30℃ and absorbed energy: vE -40℃ The target values ​​are as follows: Tensile strength: 535MPa or more Ductile fracture surface ratio: DWTTSA -30℃ : 85% or more Absorbed energy: vE -40℃ :200J or more

[0112] Furthermore, the steel structure was identified and the average grain size of bainite was calculated by the above-mentioned method.

[0113] The results are shown in Table 6.

[0114] [Table 6]

[0115] From Table 6, all of the inventive examples have a tensile strength of 535 MPa or more and a ductile fracture surface ratio of DWTTSA -30℃ : 85% or more is obtained, and it has excellent low-temperature toughness. Also, the absorbed energy: vE -40℃ It can be seen that a strength of 200J or more was obtained, and the HAZ toughness was also good.

[0116] On the other hand, in Comparative Example No. 1 in Table 6, the C and Mn contents and Ceq of the base steel sheet are below the appropriate ranges, so that the desired tensile strength is not obtained.

[0117] In the comparative example, No. 8, the C and Mn contents of the base steel plate are higher than the appropriate ranges, and the Ti content is lower than the appropriate range, so that the pinning effect of austenite by nitride formation is insufficient, and the desired HAZ toughness cannot be obtained.

[0118] In the comparative example, No. 9, the Nb and Ti contents of the base steel sheet are higher than the appropriate range, which leads to coarsening of (Ti, Nb) (C, N) and the formation of island martensite. Furthermore, the Si content is higher than the appropriate range, which promotes the formation of island martensite. As a result, the desired low temperature toughness and HAZ toughness cannot be obtained.

[0119] In the comparative example No. 10, the Nb content of the base steel plate is below the appropriate range, so the effect of suppressing the coarsening of austenite by forming carbonitrides is insufficient, and the Ca content is above the appropriate range, so that Ca-based oxides increase and the desired low-temperature toughness and HAZ toughness cannot be obtained.

[0120] In comparative example No. 21, the heating temperature in the quenching treatment was below the appropriate range, so that the austenite transformation was not completed in the base steel sheet, the final structure was non-uniform, and the desired low-temperature toughness was not obtained.

[0121] In the comparative example No. 22, the heating temperature for the quenching treatment exceeded the appropriate range, so that the Nb carbonitrides that act on austenite pinning in the base steel plate dissolved, the austenite became coarse, and the desired low-temperature toughness could not be obtained.

[0122] In comparative example No. 23, the cooling start temperature of the quenching treatment is below the appropriate range, so that ferrite is formed in the base steel sheet prior to bainite transformation, and the desired tensile strength cannot be obtained.

[0123] In the comparative example No. 24, the average cooling rate in the quenching treatment was below the appropriate range, so that the crystal grains of the transformed structure in the base steel plate became coarse, and the desired low-temperature toughness could not be obtained.

[0124] In the comparative example No. 25, the cooling stop temperature of the quenching treatment is higher than the appropriate range, so that coarse cementite and island martensite are formed in the base steel plate, and the desired low-temperature toughness cannot be obtained.

[0125] In comparative example No. 26, the tempering temperature was below the appropriate range, so that decomposition of island martensite and recovery of dislocations in the base steel plate were insufficient, and the desired low-temperature toughness was not obtained.

[0126] In the comparative example, No. 27, the tempering temperature was higher than the appropriate range, so that precipitates such as cementite in the base steel plate became coarse, and the desired low-temperature toughness was not obtained.

[0127] In the comparative examples Nos. 29, 30 and 31, the C and Nb contents of the base steel sheet exceed the appropriate range, which leads to the formation of island martensite and coarse Nb carbonitrides. Furthermore, the Si content exceeds the appropriate range, which promotes the formation of island martensite. As a result, the desired HAZ toughness cannot be obtained.

Claims

1. A clad steel plate in which a clad material is bonded to one or both sides of a base steel plate, The base steel plate comprises, in mass%, C: 0.030% or more and 0.060% or less, Si: less than 0.10%; Mn: 1.00% or more and 1.80% or less, P: 0.015% or less, S: 0.003% or less, Al: 0.010% or more and 0.070% or less, Nb: 0.005% or more and 0.060% or less, Ti: 0.005% or more and 0.030% or less, N: 0.0010% or more and 0.0060% or less, and further comprising Cu: 0.01% or more and 0.50% or less, Ni: 0.01% or more and 0.50% or less, Cr: 0.01% or more and 0.50% or less, Mo: 0.01% or more and 0.50% or less, V: 0.001% or more and 0.100% or less; Ca: 0.0005% or more and 0.0040% or less and containing one or more selected from the following: The relationship of the following formula (1) is satisfied, The balance is Fe and unavoidable impurities. Moreover, the base steel sheet is A clad steel plate having a steel structure in which, at a 1 / 2 position in the thickness direction of the base steel plate, the base steel plate has bainite at an area ratio of 80% or more and the average crystal grain size of the bainite is less than 20 μm. Note 0.40≦Ceq≦0.50 ... (1) Here, Ceq is defined by the following equation. Ceq=[C]+[Mn] / 6+([Cu]+[Ni]) / 15+([Cr]+[Mo]+[V]) / 5 Additionally, [C], [Mn], [Cu], [Ni], [Cr], [Mo] and [V] are the contents (mass%) of C, Mn, Cu, Ni, Cr, Mo and V in the base steel plate, respectively.

2. The clad steel plate according to claim 1 , wherein the clad material is a Ni-based alloy or an austenitic stainless steel.

3. A hot rolling process in which a slab formed by stacking at least one set of a material having the component composition of the base steel plate according to claim 1 and a material of a clad material is hot rolled to obtain a rolled plate containing the base steel plate and the clad material; Next, the rolled plate is heated to a temperature of 1 / 2 the thickness of the base steel plate in the thickness direction. 3 After heating, the substrate is cooled to a temperature of 1000° C. or higher and cooled to a temperature of 1000° C. or lower. 3 a quenching treatment process in which cooling is performed at a temperature of 500° C. or higher, an average cooling rate of 5° C. / s or higher, and a cooling stop temperature of 500° C. or lower at a temperature at a 1 / 2 position in the thickness direction of the base steel plate; Further, the method includes a tempering process in which the rolled plate is tempered in a temperature range of 350 ° C. or more and 650 ° C. or less at a temperature of 1 / 2 position in the thickness direction of the base steel plate, A clad steel plate in which a clad material is bonded to one or both sides of a base steel plate, A method for manufacturing a clad steel plate, wherein the base steel plate has a steel structure having bainite at an area ratio of 80% or more at a 1 / 2 position of the plate thickness in the plate thickness direction of the base steel plate, and the average crystal grain size of the bainite is less than 20 μm.

4. The method for manufacturing a clad steel plate according to claim 3, wherein the slab is formed by stacking a base steel plate material, a cladding material material, a cladding material material, and a base steel plate material in this order.

5. A line pipe using the clad steel plate according to claim 1 or 2.

Citation Information

Patent Citations

  • High strength / high toughness steel sheet and method for producing same

    WO2016157863A1

  • Clad steel sheet and production method thereof

    WO2020004410A1

  • Clad steel and method for manufacturing same

    WO2021054335A1

  • Ni ALLOY CLAD STEEL SHEET EXCELLENT IN LOW TEMPERATURE TOUGHNESS AND HAZ TOUGHNESS OF BASE MATERIAL AND CORROSION RESISTANCE OF CLADDING MATERIAL, AND METHOD OF PRODUCING THE SAME

    JP2015086422A

  • Austenitic stainless clad steel plate excellent in low temperature toughness of base material and HAZ toughness, and corrosion resistance of cladding metal and production method of the same

    JP2015105399A